Pengaruh Harga, Citra Merek Dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Piaggio Di Kecamatan Medan Marelan - Satria Mirsya Affandy Nasution; Wiby Ferdi Hendrawan. (Fisarrearch, 2021)
This study aims to analyze the effect of price on the purchase decision of a Piaggio motorcycle in the Medan Marelan sub-district. To analyze the effect of brand image on purchasing decisions for Piaggio motorbikes in Medan Marelan sub-district. To analyze the effect of promotion on the purchase decision of a Piaggio motorcycle in the Medan Marelan sub-district. To analyze the effect of price, brand image and promotion on purchasing decisions of Piaggio motorbikes in Medan Marelan sub-district. The data collection technique used in this study was to use a questionnaire. The analysis technique used is multiple linear regression, classical assumption test, t test, F test and coefficient of determination. The results showed that partially, each variable of Brand Image Price and Promotion had an effect on the Purchase Decision of a Piagiio Motorbike in Medan District and simultaneously, the variable of Brand Image Price and Promotion had an effect on the Purchase Decision of a Piagiio Motorcycle in Medan Marelan District.